High-performance symmetric supercapacitor based on molybdenum disulfide/poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) composite electrodes deposited by spray-coating - dos Santos Klem, Maykel [UNESP] (2021)
Here we present the study of supercapacitors based on molybdenum disulfide and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (MoS2/PEDOT:PSS) composite electrodes deposited by spray-coating. To produce the MoS2/PEDOT:PSS composite ink, dispersions of hydrothermally synthesized MoS2 and PEDOT:PSS were mixed in different weight proportions. Electrodes containing only PEDOT:PSS and MoS2 were also fabricated for comparison. The composite films were deposited by transferring the as-prepared inks to an airbrush coupled to a modified 3D printer base with in-line displacement. The films were characterized in terms of the scanning electron microscope (SEM), Raman spectroscopy, and sheet resistance. The electrochemical properties of supercapacitors were evaluated by cyclic voltammetry (CV), galvanostatic charge/discharges (GCD) techniques, impedance spectroscopy (IS), and their correlated parameters. The maximum specific capacitance of the MoS2-based supercapacitor was estimated to be 145.9 F g−1 at 1 mV s−1, while the 3:1 MoS2/PEDOT:PSS weight ratio supercapacitor exhibited a specific capacitance of 131.1 F g−1. Despite the slightly lower CSP, the 3:1 device provided a better overall performance, with a remarkably higher energy density of 11.2 Wh kg−1 and a maximum power density of 1020 W kg−1. It also displayed better long-term cycle stability, retaining 92% of its initial capacitance after 1000 CV cycles (against 54% of MoS2 devices). In summary, we demonstrated the study and production of a high-performance supercapacitor with spray-deposited MoS2/PEDOT:PSS composite electrodes, in which the production can be easily scalable for mass production and practical applications.